Implementing IT Processes The Main 17 IT Processes and Directions for a Successful Implementation - Pilorget, Lionel. (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2015)
Information Technology plays a major role in our society. Due to system integration and process automation, a company has to rely on performant information systems. To achieve this objective, it is important to have relevant IT processes in place on the one hand to ensure current operation and on the other hand to enable the successful introduction of new technologies. Once IT processes are defined and described, interrelations become visible, which allow to gain an appropriate level of maturity. Contents The IT Process Map - Process Dependencies - IT Governance and Process Roles - Functional Groups: Strategic Decision Making, Planning & Controlling, Account Management, Change Implementation Implementation, IT Operation & Configuration Management, Supplier Management, IT Support - Introduction of Standard IT Processes - Process Performance Indicators and Reporting - Evaluation of Process Maturity Target Group CIOs, IT Managers, IT Consultants Students of Informatics and Economics The Author Lionel Pilorget is managing projects which combine the financial, technological, and organisational dimensions. He is interested in having automated solutions in place which enable an efficient processing of complex tasks.